(untitled) (Canadian Dermatology Today, 2024)
Vitiligo is a chronic autoimmune skin disorder that affects approximately 0.5–2% of the world’s population. It is characterized by the loss of pigment-producing melanocytes, resulting in depigmented patches on the skin. Vitiligo occurs equally in all genders and across the skin colour spectrum. Although vitiligo can start at any age, 50% of affected individuals experience the onset of the condition before the age of 20. Recent developments in vitiligo research have advanced the understanding of its pathophysiology, epidemiology, and psychosocial impact on patients. While traditional treatment options have been of limited benefit, several emerging therapies are in development and may soon be available to Canadian patients with vitiligo.